A probabilistic analysis of student retention in a Federal University: A Case Study of a Computer Science Program - Santos, Marcelo S.; Claro, Daniela B.; Lima, Veronica Maria Cadena (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na Educação, 2015)
Due to the increase in inflows mainly because of REUNI procedures and low completion rates observed at a Federal University, it is necessary to identify which courses may cause the students to remain in their programs longer than expected or even leaving the university before their conclusion. In this work, we suggest that the combinations of courses in a semester may not be appropriate thus causing a student retention. We present a case study on analyzing retention rules in a Computer Science program at the Federal University of Bahia. We have estimated the retention probability and our results could help universities to better understand their programs and students.